2017
DOI: 10.1371/journal.pntd.0006056
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of a microRNA cluster in parasitic nematodes and profiling of miRNAs in excretory-secretory products and microvesicles of Haemonchus contortus

Abstract: microRNAs are small non-coding RNAs that are important regulators of gene expression in a range of animals, including nematodes. We have analysed a cluster of four miRNAs from the pathogenic nematode species Haemonchus contortus that are closely linked in the genome. We find that the cluster is conserved only in clade V parasitic nematodes and in some ascarids, but not in other clade III species nor in clade V free-living nematodes. Members of the cluster are present in parasite excretory-secretory products an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 28 publications
2
36
0
Order By: Relevance
“…Gu et al also suggest that some helminth miRNAs only might target host genes and that their release is a selective process as the profile of released miRNAs in the excretory-secretory products differed from that of adult extracts of Haemonchus contortus ( 227 ).…”
Section: Evs For the Host Immune Systemmentioning
confidence: 99%
“…Gu et al also suggest that some helminth miRNAs only might target host genes and that their release is a selective process as the profile of released miRNAs in the excretory-secretory products differed from that of adult extracts of Haemonchus contortus ( 227 ).…”
Section: Evs For the Host Immune Systemmentioning
confidence: 99%
“…In contrast to miRNAs and siRNAs, processing does not depend in Dicer ribonuclease. Following the generation of initial primary piRNAs, sequences targeting active transposons are amplified by slicing of the target RNA to give rise to secondary piRNAs (referred to as the ping-pong cycle) (Gunawardane et al, 2007). It is thought that this amplification fine-tunes the piRNA response against active transposons (reviewed in Siomi et al, 2011).…”
Section: Identification Of Pirnasmentioning
confidence: 99%
“…The recognition that exosomes are important mediators of cell-to-cell communication [ 23 , 24 ] has triggered an explosion of interest in EV biology, attributing functions to EV in an array of non-communicable and infectious diseases, whilst recognizing their diagnostic and therapeutic potential [ 25 – 28 ]. The idea that parasitic helminths secrete EV and that these vesicles function at the host parasite interface is an emerging concept with EV release from both nematode [ 29 – 33 ] and platyhelminth species [ 34 – 39 ] recently documented. We have shown that infectious L3 stage B .…”
Section: Introductionmentioning
confidence: 99%